2020
DOI: 10.1097/pq9.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Study to Understand Pediatric Hospitalists and Emergency Medicine Physicians’ Perspectives of Clinical Pathways

Abstract: Introduction: Healthcare costs are rising, and clinical pathways (CPW) are one means to promote high-value care by standardizing care and improving outcomes without compromising cost or quality. However, providers do not always follow CPW, and our understanding of their perceptions is limited. Our objective was to examine pediatric hospital medicine (PHM) and pediatric emergency medicine (PEM) physician perspectives of CPW. Methods: We conducted semistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…These findings are consistent with other studies showing that a lack of awareness of guidelines or perceived lack of evidence for measurable change represent a barrier to CP implementation [45,47,48]. Other researchers have highlighted the importance of developing educational material for clinical personnel [43], designing innovative strategies to optimize clinician education in high stress and fast-paced settings [41], and focusing on training and education as key intervention functions for enabling behaviour change [39,40].…”
Section: Knowledge Dissemination and Aligning Informationsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings are consistent with other studies showing that a lack of awareness of guidelines or perceived lack of evidence for measurable change represent a barrier to CP implementation [45,47,48]. Other researchers have highlighted the importance of developing educational material for clinical personnel [43], designing innovative strategies to optimize clinician education in high stress and fast-paced settings [41], and focusing on training and education as key intervention functions for enabling behaviour change [39,40].…”
Section: Knowledge Dissemination and Aligning Informationsupporting
confidence: 88%
“…Collaboration ensures that sites will be more motivated to achieve the goals of the CP implementation team. This finding aligns with other studies in emphasizing the importance of stakeholder engagement, including the opportunity it affords to identify early adopters or "change champions", engage senior leadership, establish consensus, and share local knowledge [41][42][43][44]. Site engagement also ensures that pertinent information about site-specific considerations are shared with the research team, such as competing priorities in the ED, changes in protocols, operational approvals, personnel changes, and local resources.…”
Section: Site Engagementsupporting
confidence: 82%
See 2 more Smart Citations
“…This standpoint gave legitimacy to decisions within the teams" (33) Environment demand (24,32,33,35,55,72,76) "Participants felt they had been thrown into the deep end when it came to implementation work" (33) Pride VBHC resource ( 24) "[…] participants were proud of their cooperation with the representatives as this contributed to the legitimacy of their implementation work" (24) complexity with new tasks in VBHC as a result of task expansion (60). The second study suggested information overload due to working with care pathways (73).…”
Section: Task Complexitymentioning
confidence: 99%